Thermal response of skin diseased tissue treated by plasmonic nanoantenna - Rasha H. Mahdi; Hussein A. Jawad (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The thermal distribution in the diseased tissue treated by different methods faces the problem of an uncontrollable defused heat. In the present article, we use a plasmonic bowtie nanoantenna working in the near infrared region to enhance the temperature confinement in the tissue. The Computer Simulation Technology Studio Suite package version 2019 was used to execute the design of both plasmonic nanoantenna and the tissue. Gold nanostructure and silicon carbide dioxide are the components the plasmonic nanoantenna in the bowtie shape. The results showed that the distance between the tumor tissue and the antenna is important to determine the intensity field where the maximum field is 5.9*107 V/m at a distance of 100 nm. The maximum specific absorption rate is 1.92*1011 W/kg at a similar distance which gives a higher temperature in the tissue of 580 Co. It is concluded that from the obtained results that the near infrared (1064 nm) resonance wavelength is recommended in the treatment of cancer cell by plasmonic bowtie nanoantenna because higher intensity field is generated. The closer distance to the nanoantenna gives higher temperature in the tissue while the temperature gradually decreases in the tissue till 400 nm where no valuable temperature was detected.